Pre-Employment Health Screening for Nurse During COVID-19 Pandemic from Occupational Health Perspective: a Document Review - Syaifoel Hardy; Isak Jurun Hans Tukayo; Edison Kabak; Akhir Fahruddin (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The COVID-19 pandemic presents a major challenge to the pre-employment health screening system for nurses looking for jobs. For this reason, a pre-employment screening system is needed that sort it easier for all parties (nurses as prospective employees, companies, and company owners) in the health screening system. To offer a health screening system in the form of Remote Pre-employment Health Screening for nurses from the occupational health nursing (OHN) perspectives. The study used  Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Analysis with qualitative descriptive methods. The documents were extracted from Google Scholar, ResearchGate, and PubMed. The indicators included respondents (nurses), research methods (mixture of quantitative, document review, case study, opinion, and report), years (2016-2021), results (focus on pre-employment health screening), and language (English). Document search used the PICOT (Population, Intervention, Comparison, Outcome, and Time) model. The search keywords were pre-employment health screening, OHN, and Covid-19. After analyzing the documents in the database (n=702), the records were eligible (n=10), and met the requirements for review (n=7). The findings of reviewed records were that the pandemic caused a disastrous impact on the nursing profession including the need to review the pre-employment health screening system. To prepare a remote pre-employment health screening system, the study suggests organization to a three in one formula: to make a memorandum of understanding, to set health examination standards, and to create an electronic application.   Keywords: Pre-employment, health screening, OHN, occupational healthCovid-19.